Big flame : . Big flame : Merseyside socialist newspaper
Merged with: Libertarian communist. Paper of the Libertarian communist group (ZF 60343). - Also subtitled: Merseyside socialist newspaper, Merseyside revolutionary socialst newspaper, Monthly paper of the Revolutionary Socialist Organisation Big Flame, Merseyside edition, Monthly paper of the Revolutionary Socialist Organisation Big Flame, Manchester edition. - See also: Big Flame journal (ZDK 39383), and: Revolutionary socialism (ZK 44547).